La ricerca antropologica fra immaginari umanitari e capacità di resilienza - Costa, Chiara; Tisci, Rossella (Antropologia Pubblica, 2024)
This research aims at discussing the role of the researcher in dealing with the ethical dilemmas of international cooperation. From one side NGOs promote the building of a society encompassing social justice and human rights; from the other, the strategies implemented by them to get the funds indispensable for keeping their development projects alive not always respect the above-mentioned values. In other words, there is a dissonance between what NGOs advocate about human rights, social justice, equal rights, active involvement and what they endorse in terms of public propaganda. The trend to promote simplified and generalized issues for purposes linked to NGOs economic goals weakened the universal imaginary of human rights and increased the skepticism around international development projects and promotion. This scenario represents a challenge for ethically sensitive researchers – as well as journalists – who have to undertake some specific research strategies and methods to keep fair features in their analyses. In this paper – through the evidences resulting from a fieldwork in a Cambodian slum – it will be claimed that an ethically sensitive research needs a participatory framework. The adoption of participatory research methods – involving people in all the phases of the research process – not only lets the researcher focus the research on people’s real goals, needs and values but it also provides people with awareness about their own opportunities and potentialities.